Arbuscular mycorrhizal colonization defines root ecological strategies in an extreme arid environment - Delpiano, Cristian A.; Rios, Rodrigo S.; Barraza-Zepeda, Claudia E.; Pozo, Melissa J.; Aguilera, Lorgio E.; Loayza, Andrea P. (Frontiers in Plant Science, 2025)
The symbiosis between mycorrhizae fungi and plant roots is essential for plant establishment in nearly all terrestrial ecosystems. However, the role of mycorrhizal colonization (colM) in shaping root ecological strategies remains poorly understood. Emerging research identifies colM as a key trait influencing the multidimensional covariation of root traits within the Root Economic Space (RES), where a ‘collaboration gradient’ is proposed. At one end of this gradient, species with larger root diameters (RD) rely on colM for resource acquisition through an ‘outsourcing’ strategy, while at the other end, species with finer roots and greater exploration capacity employ a ‘do it yourself’ strategy to acquire resources independently. Although the RES framework has improved our understanding of root strategies, the relationship between colM and root traits in desert ecosystems remains underexplored, particularly in hyper-arid environments, where limited resources can constrain both plant and mycorrhizal survival. In this study, we examine the root ecological strategies of 32 dominant shrub species in Chile’s Coastal Atacama Desert, focusing on the link between specific root traits and colM. We found that larger RD correlated with higher levels of colM, supporting the ‘outsourcing’ strategy within the ‘collaboration gradient’ hypothesis of the RES. Additionally, RD and colM emerged as playing key roles in defining both dimensions of root ecological strategies. Moreover, we identified colM as a central hub trait in the root phenotypic network, underscoring its role in survival strategies under hyper-arid conditions. These findings emphasize the critical importance of colM in modulating plant ecological strategies and highlight the need to further investigate how AM enhances root lifespan and optimizes resource uptake in extreme environments.